2022
DOI: 10.1101/2022.11.12.516264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small proteome of the nitrogen-fixing plant symbiontSinorhizobium meliloti

Abstract: The soil-dwelling plant symbiont Sinorhizobium meliloti is a major model organism of Alphaproteobacteria. Despite numerous detailed OMICS studies, information about small open reading frame (sORF)-encoded proteins (SEPs) is largely missing, because sORFs are poorly annotated, and SEPs are hard to detect experimentally. However, given that SEPs can fulfill important functions, cataloging the full complement of translated sORFs is critical for analyzing their roles in bacterial physiology. Ribosome profiling (Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
1
0
0
Order By: Relevance
“…92,93 Advanced detection strategies also revealed novel small proteins in other species such as the archaeon Haloferax volcanii, the nitrogen-fixing plant symbiont Sinorhizobium meliloti, Salmonella Typhimurium and Staphylococcus aureus. [33][34][35]94 Among the previously known sORFs in E. coli K-12 and those discovered by Weaver et al 92 pH-dependent differential RPF levels were observed in our datasets for 12 and 29 small proteins at pH 5.8 and pH 4.4 respectively (Table S8). These findings validate the expression of these sORFs and highlight their physiological relevance in the acid stress response of E. coli.…”
Section: Differential Expression Of Known and Identification Of Novel...supporting
confidence: 54%
“…92,93 Advanced detection strategies also revealed novel small proteins in other species such as the archaeon Haloferax volcanii, the nitrogen-fixing plant symbiont Sinorhizobium meliloti, Salmonella Typhimurium and Staphylococcus aureus. [33][34][35]94 Among the previously known sORFs in E. coli K-12 and those discovered by Weaver et al 92 pH-dependent differential RPF levels were observed in our datasets for 12 and 29 small proteins at pH 5.8 and pH 4.4 respectively (Table S8). These findings validate the expression of these sORFs and highlight their physiological relevance in the acid stress response of E. coli.…”
Section: Differential Expression Of Known and Identification Of Novel...supporting
confidence: 54%